Characterization of spray deposition and drift from a low drift nozzle for aerial application at different application altitudes - Huang, Yanbo; Thomson, Steven J. (International Journal of Agricultural and Biological Engineering, 2012)
A complex interaction of controllable and uncontrollable factors is involved in aerial application of crop production and protection materials. ?Although it is difficult to completely characterize spray deposition and drift, these important factors can be estimated with appropriate sampling protocol and analysis. ?Application height is an important variable influencing off-target spray drift, but this variable has not been easily measured or logged. A custom-configured aircraft-mounted laser with logging capabilities makes this possible. ?This study was designed to investigate droplet size and deposition characteristics of a low drift CP flat-fan nozzle at application altitudes 3.7 m, 4.9 m, and 6.1 m. In the study, CP flat-fan nozzles were set to a downward angle of 30 degrees applying a mixture of water, Syl-Tac? adjuvant, and Rubidium Chloride (RbCl) tracer at a ?28.5 L/ha application rate.? Spray droplets were collected using water sensitive paper (WSP) cards placed in the spray swath. Mylar sheets were also placed in the swath and downwind for drift sampling. Statistical analysis indicated that median droplet diameter as determined by WSP in the spray swath was not significantly influenced by spray application height. ?Similarly, statistical analysis also indicated that concentration of RbCl tracer from Mylar samplers in the spray swath was not significantly influenced by application height. ?Application height had a significant effect on spray deposition from drift samplers, along with wind direction and relative humidity. ?Final results for drift samplers may have been influenced by shifts in wind direction that altered the relationship between orientation of samplers and wind. Keywords: deposition, spray nozzle, aerial application, droplet spectra, spray drift DOI: 10.3965/j.issn.1934-6344.2011.04.028-033 ? Citation: Huang Y, Thomson S J. ?Characterization of spray deposition and drift from a low drift nozzle for aerial application at different application altitudes. ?Int J Agric & Biol Eng, 2011; 4(4): 28